Analysis of reform scenarios for telecommunications sector in Vietnam - Nguyen Huy Tuan; Do, Ba Khang; Krishnamurthy Ramanathan; Erke, Tapio J.; Okumenisches Studienwerk e:V. Bochum (OSW) (Bangkok : Asian Institute of Technology, 1997)
Telecommunication is an imp01iant infrastructure in today's global economy and has rightly been recognized as the catalyst for socio-economic growth and competitiveness. A rapidly growing number of developing countries, including Vietnam, are in the process of revising the structure of their telecommunications sector for a variety of reasons ranging from improving efficiency and upgrading infrastructure, to supp01iing macro economic reform objectives. Hard pressed to attract domestic and foreign investment to upgrade the inadequate infrastructure and inspired by developments and reform efforts in the neighboring countries, the Vietnamese government faces the daunting task of further opening the sector for development without loosing its control over the whole reform process. A study was conducted to address the reforms in the telecommunications sector of Vietnam that are based on four distinct but inter.related policy variables of competition, regulation, restructuring and ownership. A detailed situational analysis was carried out in order to identify the aims, goals, constraints and objectives of the reform in the telecommunications sector of Vietnam. Four scenarios of reform were then developed, based on the four key decisions, namely separation of the posts and the telecommunications, formation of regional operating companies, introduction of competition and changing of ownership. Out these scenarios, the first two key decisions are definitely established. The alternative scenarios for reform were assessed according to the objectives of the reform. It was found that no one option fulfills the objectives of the reform in the telecommunications sector. The reforms in the telecommunications sector of Vietnam should be carried out on phase-basis. Out of the four scenarios, the best option in the initial phase of reform (short and medium term) will be corporatization of the operator and the introduction of competition in some selected areas along with the formation of regional operating companies and the separation of posts and telecommunications. Only after strengthening of this initial phase, privatization at the regional level should follow as long-term strategy.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research studies project report (M.BA.) - Asian Institute of Technology, 1997
Keywords: Telecommunication -- Vietnam